Analisis Kualitas Pelayanan Akademik dalam Meningkatkan Mutu Lulusan Tepat Waktu - Muhamad Januaripin (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Students play an important role in evaluating the success and validity of a study program in a higher education environment. The success of a higher education institution can be measured by the achievements achieved by its graduates. Students who pursue a Bachelor (S1) program are considered to graduate on time if they successfully complete their studies in four years or less. Internal and external factors, as well as the quality of academic service, are factors that can affect student graduation on time. This research aims to find out how STAI Miftahul Huda Subang alumni, especially those who take the Study Program (S1) Islamic Religious Education (PAI), see academic guidance services to improve the quality of graduates. This research uses a quantitative descriptive approach and uses survey methods. Data is collected through observations, interviews, lifts, and documentation. The results of this study show that the quality of academic service at STAI Miftahul Huda Subang is already good in terms of student perception. In order to improve the quality of academic services, STAI Miftahul Huda Subang needs to improve educational facilities and the discipline of lecturers in teaching. In addition, Stai Miftahul Huda Subang also needs to cooperate with the insurance authorities to guarantee the safety and comfort of students during the course.